Audit of compliance with antenatal protocols. - Yoong, A. F. (1992)
OBJECTIVE--To assess the implementation of action protocols dictated by antenatal risk factors noted at the initial (booking) antenatal visit. DESIGN--Retrospective study of 2000 women delivered between 1 March 1990 and 29 March 1991. SETTING--Maternity department of a district general hospital supporting a multiethnic population in inner London. MAIN OUTCOME MEASURES--Comparison of clinical actions performed against those dictated by the department's protocols. Analysis according to clinical importance, gestation at booking, maternal age, parity, birth order, ethnic origin, and certainty of gestational age. RESULTS--Interobserver agreement between the two auditors was good (kappa statistic for risk factors detected, 0.78; for actions generated, 0.80). Of the 15,658 actions dictated by department protocols, 3673 (23.5%) were actually performed by the clinicians. The 63 combinations of risk factors and actions believed by consultants to be of particular clinical importance had an action rate of 28.3% compared with 18.6% for those considered less important (p < 0.001). Mothers who first visited the hospital antenatal clinic at or before 24 weeks' gestation had 25.2% of relevant protocols fulfilled (p < 0.001). Compliance was significantly improved in women aged 36 or over (32.4%), black women (24.9%), and cases of uncertain gestation (24.5%). Parity and birth order were not associated with an altered action rate. Ethnic origin deemed as "other" (than white, black, Asian, or oriental) or "unknown" was associated with poor compliance (19.3%). CONCLUSIONS--Compliance to a set of agreed protocols was poor even though a computer system was available and a protocol manual had been distributed. Protocols were more likely to be implemented in women who booked early and in some groups of women deemed at high risk including older mothers, black women, and those denoted as having uncertain gestational age.